Analisis Rasio Likuditas, Solvabilitas, Aktivitas Dan Profitabilitas Untuk Menilai Kinerja Keuangan Pada Perusahaan Food And Beverage Yang Terdaftar Di Bursa Efek Indonesia Tahun 2019-2021 - Ningsih, Ana Mardiana; hardiwinoto, hardiwinoto; ridwan, mohammad; putri, anindya p.r.z (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2023)
The power to manifest profits to a company is considered to be the key to success in creating good decisions about a company's financial performance. This current research aims to empirically prove the relationship between liquidity ratios, solvency, activity, profitability, and financial performance. The objective of this study is to statistically show whether liquidity, solvency, activity and profitability affects financial performance. This research uses secondary data that is obtained from food and beverage companies' financial reports that are listed from the Indonesian Stock Exchange between 2019-2021 time period. Determinants are analyzed using multiple linear regression methods using SPSS ver.26. The results of this research proves that solvency and activities affect financial performance, while liquidity and profitability do not affect financial performance. The difference between this study and previous research by Rumina and Desy (2021) is the addition of independent variables, namely solvency and activity variables.